Pengembangan Media Pembelajaran Video Interaktif Menggunakan Canva Untuk Keindahan Kebersamaan Di Sekolah Dasar - Muhamad Fadhil Ismayana; Resyi A. Gani; Dendy Saeful Zen Musbihinal Fitrah (PT. Banjarese Pacific Indonesia, 2023)
This research aims to determine the development of interactive video learning media using Canva for class IV students at SDN Bojong 03 and the feasibility of interactive video learning media using Canva for the learning process at school. The method used in this research is the ADDIE method which consists of 5 stages, namely Analysis, Design, Development, Implementation, and evaluation. In this research, validation tests were carried out on experts, namely media experts, language experts, and material experts. The validation results from media experts obtained 83% with very feasible criteria. The linguist's validation results were 100% with very feasible criteria. The material expert validation results were 94.4% with very feasible criteria. The results of the student response questionnaire were 97.4% with very adequate criteria. These results show that interactive video learning media using Canva on theme 1 the Beauty of Togetherness subtheme 1 learning 1 is proven valid, interesting, innovative, and very suitable for use in the learning process.